A Novel Gametocyte Biomarker for Superior Molecular Detection of the Plasmodium falciparum Infectious Reservoirs. (24th August 2017) - Essuman, Edward; Grabias, Bryan; Verma, Nitin; Chorazeczewski, Joanna K; Tripathi, Abhai K; Mlambo, Godfree; Addison, Ebenezer A; Amoah, Albert G B; Quakyi, Isabella; Oakley, Miranda S; Kumar, Sanjai
Abstract : We have identified a superior diagnostic biomarker, Pfg17, for detecting asymptomatic reservoirs otherwise missed by the most sensitive molecular method available. Gametocyte transcriptome analyses also improved the repertoire of transmission-stage antigens available for evaluation as candidate vaccines. Abstract: Background: Complete malaria eradication and optimal use of transmission-reducing interventions require knowledge of submicroscopic infectious reservoirs among asymptomatic individuals. Even submicroscopic levels of Plasmodium falciparum gametocytes can infect mosquitoes and promote onward transmission. Most efforts to identify gametocyte carriers use polymerase chain reaction amplification of the gametocyte-specific transcript Pfs25. Methods: To expand the repertoire of biomarkers available for superior gametocyte detection, we compared the gene expression profiles of gametocytes and asynchronous blood-stage P. falciparum parasites by microarray technology. This allowed the identification of 56 molecules abundantly expressed in the gametocyte stage of the parasite. The analytical sensitivity for gametocyte detection was evaluated for 25 genes with the highest expression levels. Results: One candidate, Pfg17, exhibited superior analytical sensitivity against a panel of gametocyte-spiked whole blood, detecting 10 gametocytes/mL; in comparison, Pfs25 detected only 25.3 gametocytes/mL. Pfg17 also exhibited superior clinical sensitivity, identifying 19.1% more samples from blood-film microscopy–negative Ghanaian children and 40% more samples from asymptomatic adults as gametocyte positive. Conclusions: Cumulatively, our results suggest Pfg17 is an excellent biomarker for detecting asymptomatic infectious reservoirs otherwise missed by the most sensitive molecular method available. Our study has also improved the repertoire of transmission-stage antigens available for evaluation as candidate vaccines.